THE VALUE CHAINS OF HIGH-TECHNOLOGY PRODUCTS AS FACTOR OF FORMATION OF THE REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP - I. A. Safronova (Vestnik MGIMO-Universiteta)
This article analyzes the value chain of high-tech products in Asia and the role of this phenomenon in the further consolidation of trade blocs and alliances in the region. The presence of these chains and their gradual transition from a vertically integrated model to a system of horizontal linkages and interdependence leads to the formation of mechanisms of economic de-facto integration (so-called regionalization process). The East Asian region has demonstrated unprecedented high rates of economic growth in recent decades. The countries are actively developing mechanisms of multilateral cooperation, involving partners from across the Asia-Pacific region. Particular features of a new regional architecture of economic relations are becoming more tangible, and the essential element of this architecture is the intra-regional integration. The author presents an assessment of further developments of the Regional comprehensive economic partnership (RCEP) using the structural-functional approach and analytical instruments of the international political economy, The creation of this trade block will help less advanced countries of ASEAN to accelerate economic growth and improve the conditions for integration into global value chains. For advanced economies, participation in the RCEP seems controversial, because production chains have well-established formats within the framework of ASEAN +. The political standoff between Washington and Beijing has an impact on dynamics of regional integration. The split among the East Asian countries was galvanized by the Trans-Pacific Partnership Project (TTP), because TPP has objectives that are very similar to those of RCEP (trade liberalization and economic integration). The author concludes that the extension of this partnership in the ASEAN countries can seriously complicate the operation RVEP and enhance the impact of political factors on economic cooperation. In this case, the value of production and supply chains of high-tech products will decline, which may affect the economic cooperation in the region as a whole.